2020
DOI: 10.1111/dth.14077
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of methotrexate as add on therapy to H1 antihistamine in difficult to treat chronic urticaria: A systematic review and meta‐analysis of randomized clinical trials

Abstract: A systematic review and meta-analysis of randomized clinical trials (RCTs) to evaluate efficacy of add on methotrexate in chronic urticaria. "PubMed" and "Google Scholar" were systematically searched to identify randomized clinical trials with methotrexate in patients with chronic urticaria not responding to second generation antihistamines. Odds ratios and 95% confidence interval were calculated for estimation of efficacy. Heterogeneity among studies was tested using Tau squared (τ 2) and I 2. Two RCTs (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(55 reference statements)
2
4
0
Order By: Relevance
“…As a result, we judged the use of cyclosporine as providing a small beneficial effect. Taken together, our network estimates and the review by Patil et al also noted no significant benefit of methotrexate for the treatment of CSU in individuals who are refractory to H 1 antihistamine therapy.…”
Section: Discussionsupporting
confidence: 73%
“…As a result, we judged the use of cyclosporine as providing a small beneficial effect. Taken together, our network estimates and the review by Patil et al also noted no significant benefit of methotrexate for the treatment of CSU in individuals who are refractory to H 1 antihistamine therapy.…”
Section: Discussionsupporting
confidence: 73%
“…Another intriguing finding was that the efficacy of methotrexate was found to be weaker than a placebo in CSU management. In fact, this result was also supported by a previous systematic review and meta-analysis, which found that there was no significant benefit of adding methotrexate to an antihistamine in refractory urticaria management [ 50 ]. Due to limited adequate references of methotrexate in CSU management, there was only one clinical trial that met our inclusion criteria for inclusion in our quantitative analysis.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, a systematic review of the effects of add-on methotrexate has been reported by Patil et al; they concluded that though well tolerated, there may be no add-on benefit of methotrexate in difficult to treat urticaria with the caveat that this recommendation is based on limited data. 26 Current Indian guidelines still recommend methotrexate, even with the paucity of good evidence, due to its suitability from the Indian perspective with respect to cost, availability, dosing schedule and good acceptance. 27 On reviewing the available literature, we concur that application of methotrexate may be limited to cases where antihistamines have failed or the patient may have become steroiddependent.…”
Section: Discussionmentioning
confidence: 99%